2018
DOI: 10.3928/00220124-20180417-08
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Registered Nurses' Perceptions of Their Professional Identity: An Integrative Literature Review

Abstract: This integrative review identified a lack of research addressing how nurses' perceptions of their professional identity change over time. A deeper understanding of their perspective is needed to establish whether career longevity and continued professional development are influences. J Contin Educ Nurs. 2018;49(5):225-232.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
97
0
19

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(122 citation statements)
references
References 21 publications
6
97
0
19
Order By: Relevance
“…The change of social and working environment of nurses could be the underlying mechanisms. Rasmussen et al reviewed contemporary studies and concluded that factors influencing nurses’ perceptions of their professional identity were synthesized into three categories: the self (who I am), the role (what I do), and the context (where I do) ( Rasmussen, Henderson, Andrew & Conroy, 2018 ). This shows that the perception of oneself and outside world is essential for professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…The change of social and working environment of nurses could be the underlying mechanisms. Rasmussen et al reviewed contemporary studies and concluded that factors influencing nurses’ perceptions of their professional identity were synthesized into three categories: the self (who I am), the role (what I do), and the context (where I do) ( Rasmussen, Henderson, Andrew & Conroy, 2018 ). This shows that the perception of oneself and outside world is essential for professional identity.…”
Section: Discussionmentioning
confidence: 99%
“…It is a component of people overall identity and is augmented by the 'position within society', 'interactions with others' and their 'interpretations of experiences' [14]. The perception of professional identity varies among individuals, as experience and understanding are different among practitioners [15]. Professional identity has been identified as a key factor in GPs' ability to provide high-quality care to improve patient outcomes [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that excessive pressure damages the professional identity and health condition of nurses, and may affect their attitudes toward patients as well as their nursing behavior, and these adverse impacts have the potential to harm the relationship between nurses and patients and degrade the quality of care (Johnson, Cowin, Wilson, & Young, 2012; Rasmussen, Henderson, Andrew, & Conroy, 2018; Wu, Zhu, Wang, Wang, & Lan, 2007). In the context of the COVID‐19 pandemic, high infection risk, heavy workload and medical supply shortage may induce excessive pressure on nurses and negative emotions such as tension and anxiety (Mo et al, 2020; Zhang et al, 2020).…”
Section: Figurementioning
confidence: 99%